Застосування штучного інтелекту для автоматизації роботизованих процесів - Суботін, О. В.; Новіков, Д. С. (Видавництво "Молодий вчений", 2025)
У статті досліджено можливості застосування штучного інтелекту (ШІ) для автоматизації роботизованих процесів, а також опрацьовано основні технологічні рішення, що забезпечують інтеграцію інтелектуальних систем у сучасне виробництво. Проаналізовано вплив алгоритмів ШІ на підвищення ефективності, адаптивності та автономності робототехнічних комплексів у різних сферах. У статті розглядаються основні підходи до впровадження алгоритмів ШІ, зокрема машинного навчання, глибинного навчання та нейронних мереж, у контексті автоматизації складних і динамічних задач. Окрема увага приділяється аналізу практичних кейсів використання ШІ для управління мобільними роботами, оптимізації маршрутів, адаптивного планування дій та виявлення несправностей у реальному часі. Розкрито потенціал використання технологій ШІ для створення гнучких виробничих систем, здатних до самонавчання та прийняття рішень без втручання людини. Висвітлюються переваги, виклики та перспективи, пов’язані з інтеграцією ШІ у сферу роботизованої автоматизації, а також окреслено напрямки подальших досліджень у цій галузі.

The article presents a comprehensive examination of the potential applications of artificial intelligence (AI) in the automation of robotized and intelligent industrial processes. It explores how AI-driven systems are increasingly becoming an essential component in enhancing the performance, efficiency, and adaptability of modern robotics within diverse sectors of industry. By focusing on key technological enablers, the study delves into the integration of intelligent control algorithms, sensor fusion, and real-time data analytics into automated manufacturing environments. Special emphasis is placed on the role of AI in transforming traditional robotics into highly autonomous systems capable of learning from experience and adapting to unpredictable environments. The paper systematically reviews foundational approaches for implementing AI technologies, including machine learning algorithms, deep learning architectures, neural networks, reinforcement learning, and hybrid models, in the context of complex robotic operations. These approaches allow robots to go beyond pre-programmed behavior and respond dynamically to environmental changes. Additionally, practical case studies illustrate the successful application of AI for mobile robot navigation, route optimization in dynamic environments, adaptive decision-making, obstacle avoidance, fault detection, and predictive diagnostics. The article highlights the importance of advanced perception systems, such as AI-powered computer vision and multimodal sensor integration, which enable robots to interpret their surroundings with high accuracy and precision. Moreover, the research outlines how AI contributes to the development of flexible manufacturing systems that are capable of self-configuration, autonomous task execution, and decision-making without direct human oversight. Such systems can continuously monitor production conditions, reallocate resources efficiently, and anticipate maintenance needs based on predictive models. These capabilities result in enhanced productivity, reduced downtime, and increased operational resilience. The study also investigates the broader implications of integrating AI into robotic automation, including ethical considerations, the challenge of ensuring transparency and explainability in AI-driven decisions, and the need for robust cybersecurity measures. It emphasizes that the synergy between AI and robotics is not only a matter of technological evolution but a strategic imperative for industries striving to maintain competitiveness in the era of digital transformation and Industry 4.0. In conclusion, the findings suggest that AI is reshaping the future of automation, making robotic systems more intelligent, autonomous, scalable, and capable of performing complex tasks under varying conditions. The paper calls for continued interdisciplinary research and innovation to fully unlock the transformative potential of AI in next-generation automated systems.
Application of artificial intelligence for the automation of robotized processes
Keywords: сучасні технології; штучний інтелект; автоматизація роботизованих процесів; оптичне розпізнавання символів; машинне навчання; modern technologies; artificial intelligence; automation of robotized processes; optical character recognition; machine learning